DYNAMICS OF ISLAMIC STUDIES IN THE DIGITAL ERA BETWEEN CHALLENGES AND OPPORTUNITIES - Luthfi, Atabik (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The digital era has significantly transformed various fields, including Islamic studies. This study explores the dynamics of Islamic studies in the digital age, highlighting the challenges and opportunities faced by academics, students, and Islamic educational institutions. With the rise of digital connectivity, access to Islamic knowledge has become more widespread and easily available through online platforms, social media, and learning applications. However, alongside these advancements, challenges have emerged, including the spread of inaccurate information, potential distortion of Islamic teachings, and the rise of superficial understandings of Islam. This study employs a qualitative approach, utilizing literature analysis and in-depth interviews with experts in Islamic education. The findings indicate that while issues related to the validity and authority of knowledge sources remain significant, the digital era also presents valuable opportunities. These include fostering global collaboration, expanding access to Islamic education for broader communities, and developing more interactive and innovative learning methods.